Use of quantitative T2 mapping for the assessment of renal cell carcinomas: First results - Adams, Lisa C.; Bressem, Keno K.; Jurmeister, Phillipp; Fahlenkamp, Ute L.; Ralla, Bernhard; Engel, Guenther; Hamm, Bernd; Busch, Jonas; Makowski, Marcus R. (Cancer Imaging, 2019)
Background: Correct staging and grading of patients with clear cell renal cell carcinoma (cRCC) is of clinical relevance for the prediction of operability and for individualized patient management. As partial or radial resection with postoperative tumor grading currently remain the methods of choice for the classification of cRCC, non-invasive preoperative alternatives to differentiate lower grade from higher grade cRCC would be beneficial. Methods: This institutional-review-board approved cross-sectional study included twenty-seven patients (8 women, mean age ± SD, 61.3 ± 14.2) with histopathologically confirmed cRCC, graded according to the International Society of Urological Pathology (ISUP). A native, balanced steady-state free precession T2 mapping sequence (TrueFISP) was performed at 1.5 T. Quantitative T2 values were measured with circular 2D ROIs in the solid tumor portion and also in the normal renal parenchyma (cortex and medulla). To estimate the optimal cut-off T2 value for identifying lower grade cRCC, a Receiver Operating Characteristic Curve (ROC) analysis was performed and sensitivity and specificity were calculated. Students' t-tests were used to evaluate the differences in mean values for continuous variables, while intergroup differences were tested for significance with two-tailed Mann-Whitney-U tests. Results: There were significant differences between the T2 values for lower grade (ISUP 1-2) and higher grade (ISUP 3-4) cRCC (p < 0.001), with higher T2 values for lower grade cRCC compared to higher grade cRCC. The sensitivity and specificity for the differentiation of lower grade from higher grade tumors were 83.3% (95% CI: 0.59-0.96) and 88.9% (95% CI: 0.52-1.00), respectively, using a threshold value of ≥110 ms. Intraobserver/interobserver agreement for T2 measurements was excellent/substantial. Conclusions: Native T2 mapping based on a balanced steady-state free precession MR sequence might support an image-based distinction between lower and higher grade cRCC in a two-tier-system and could be a helpful addition to multiparametric imaging.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Clear cell renal cell carcinoma; MRI mapping techniques; Quantitative MRI; T2 mapping; Tumor grading